Adsorption of polyvinylpyrrolidone and polyoxyethylene by pure and mixed silicon, aluminium and titanium oxides - Voronin, E. F.; Guzenko, N. V.; Gun'ko, V. M.; Malysheva, M. L.; Pakhlov, E. M.; Eremenko, B. V.; Chuiko, A. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2002)
Adsorption of polyvinylpyrrolidone (PVP) and polyoxyethylene (POE) from the aqueous solutions onto surfaces of individual and mixed silicon, titanium and aluminium oxides was studied. It was found that the values of polymer adsorption depend on composition of oxides. It was shown with IR spectroscopy that the surface of the oxides studied is fully accessible to interaction with PVP and POE.